Revision of Physobates (Acari, Oribatida, Tegoribatidae) and redescription of Physobates spinipes Hammer, 1962 with comments on tegoribatid genera - Fredes, Natalia A.; Martínez, Pablo A. (Zootaxa, 2016)
Herein we review the genus Physobates Hammer, 1962 and redescribe P. spinipes Hammer 1962 based on material collected in Buenos Aires, Argentina. After a morphological comparison among species of Tegoribatidae genera, we propose a new junior synonym, Paraphysobates Mahunka, 1985. A key to identify tegoribatid genera is also provided.